2011
DOI: 10.1021/jf202452m
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Lignopolyols from Wheat Straw Soda Lignin

Abstract: Wheat straw soda lignin was modified and characterized by several qualitative and quantitative methods such as 31 P NMR spectroscopy to evaluate its potential as a substitute for polyols in view of polyurethane applications. Chemical modification of the lignin was achieved with propylene oxide to form lignopolyol derivatives. This was performed by a two-step reaction of lignin with maleic anhydride followed by propylene oxide and by direct oxyalkylation under acidic and alkaline conditions. The physical and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
87
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 25 publications
7
87
0
5
Order By: Relevance
“…As a result of the direct oxyalkylation with PC, lignin polyols with exclusively aliphatic OH groups were generated. This OH profile was similar to that of lignin polyols synthesized by oxyalkylation with PO (Ahvazi et al 2011;Sadeghifar et al 2012).…”
Section: Direct Oxyalkylation Of Ligninsupporting
confidence: 67%
See 1 more Smart Citation
“…As a result of the direct oxyalkylation with PC, lignin polyols with exclusively aliphatic OH groups were generated. This OH profile was similar to that of lignin polyols synthesized by oxyalkylation with PO (Ahvazi et al 2011;Sadeghifar et al 2012).…”
Section: Direct Oxyalkylation Of Ligninsupporting
confidence: 67%
“…In contrast to the oxyalkylation with PO, the carboxylic acids of the maleated lignin were not completely hydroxypropylated (Ahvazi et al 2011). In analogy to the spectrum of hOL, two distinct broad signals were seen in the aliphatic region, which can be assigned to the remaining OH groups in OL (146.5-149.5 ppm) and the hydroxypropyl OH groups (145.5-146.5 ppm).…”
Section: Two-step Oxyalkylation Of Ligninmentioning
confidence: 93%
“…Esterification of lignin using e-caprolactone, maleic anhydride, and succinic anhydride can be carried out to increase the reactivity for the production of lignin-based epoxy resins [135][136][137] and polyurethanes [138].…”
Section: Esterificationmentioning
confidence: 99%
“…Several studies have suggested that the solubility and uniformity of the lignin are the key parameters that affect its reactivity as a substitute for polyol in PU fabrication (Hsu and Glasser 1976;Saraf et al 1985;Rials and Glasser 1986;Mörck et al 1988;Ciobanu et al 2004;Hatakeyama et al 2008). Lignin substitution in PU could be achieved directly by the combination with polyol (Yoshida et al 1990;Evtuguin et al 1998;Vanderlaan and Thring 1998;Cateto et al 2008) or through chemical modifications (Glasser 1989;Gandini et al 2002;Nadji et al 2005;Ahvazi et al 2011).…”
Section: Introductionmentioning
confidence: 99%